A Study on the Addition of Sweet Orange (Citrus sinensis L) to Reduce Goaty Odor in Goat Milk-Based Yogurt - Annisa Desfi; Della Rosalynna Stiadi; Nurul Aulia; Rahma Dika Aulia Nasution (Study Program of Chemistry, Faculty of Mathematics and Natural Sciences, Universitas Pakuan, 2024)
This study aimed to reduce the goaty odor in goat milk yogurt by adding sweet orange (Citrus sinensis L). Yogurt was prepared with varying concentrations of sweet orange: 0%, 5%, 10%, and 15% (v/v). The yogurt characteristics analyzed included organoleptic properties, pH, lactic acid, protein, and moisture content. Results showed that adding 15% sweet orange was most effective in reducing goaty odor and increasing consumer preference. The yogurt pH remained stable at 4, while lactic acid content increased to 1.35% compared to the control (1.26%). Protein content decreased with increasing orange concentration, while moisture content increased. This study concludes that adding sweet oranges effectively reduces the goaty odor in goat milk yogurt, although attention should be paid to the decrease in protein content. These findings open opportunities for developing more appealing goat milk yogurt products for Indonesian consumers.